Effect of Natural Fiber Stacking Sequence on the Properties of Hybrid Composites for Drone Frame Applications - Janiviter Manalu; Jefri Bale; Khristhoper Aris Arianto Manalu; Frans Augusthinus Asmuruf; Fitriyana, Deni Fajar; Nizar Alamsyah; Januar Parlaungan Siregar; Al Ichlas Imran; Tezara Cionita; Natalino Fonseca Da Silva Guterres (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
The present study highlights the effective utilization of waste fibers in structural composites for drone frame applications, offering a sustainable pathway for developing high-performance materials while simultaneously addressing the issue of textile waste pollution. This study investigates the effect of ramie and cotton fiber waste fabric stacking sequences on the physical and mechanical properties of composites for quadcopter drone frames. Waste fabric was selected as an eco-friendly material to address textile pollution. The composites were fabricated using the hand lay-up technique with a 3:1 epoxy resin to hardener ratio, incorporating five layers of fabric in different configurations. The physical and mechanical properties, including density, water absorption, material hardness, flexural strength, and macro photography, were tested. The results showed that the composite made from fully cotton fabric (K-K-K-K-K) had the best density (1.182 g/cm³), lowest water absorption (2.22%), highest hardness (85.6 HD), and flexural strength of 179.1 MPa. These findings indicate that cotton fabric waste is a promising, sustainable material for composite reinforcement in quadcopter drone frame applications.